Z dziejów bowaryzmu we Francji - Staroń, Anita (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
The first mention of the term “bovarism” appears shortly after the release of Flaubert’s novel, but the modern definition: “to perceive oneself differently than one is in reality”, was coined by the philosopher and critic Jules de Gaultier. He made bovarism the center of his concept of the modern man, or even of the modern society, and he dedicated 20 years of his life to its analysis. With time, he grew to understand that it was not only a pathology, but also the moving force of human actions. Many other researchers pursued the topic of bovarism after Gaultier, both in literature and in medicine spheres. Today the concept is still popular and used not exclusively in literature, but also in social and political meaning.